Protein engineering strategies for improving the selective methylation of target CpG sites by a dCas9-directed cytosine methyltransferase in bacteria. - Tina Xiong; Dahlia Rohm; Rachael E Workman; Lauren Roundtree; Carl D Novina; Winston Timp; Marc Ostermeier (PLoS ONE, 2018)
Mammalian gene expression is a complex process regulated in part by CpG methylation. The ability to target methylation for de novo gene regulation could have therapeutic and research applications. We have previously developed a dCas9-MC/MN protein for targeting CpG methylation. dCas9-MC/MN is composed of an artificially split M.SssI methyltransferase (MC/MN), with the MC fragment fused to a nuclease-null CRISPR/Cas9 (dCas9). Guide RNAs directed dCas9-MC/MN to methylate target sites in E. coli and human cells but also caused some low-level off-target methylation. Here, in E. coli, we show that shortening the dCas9-MC linker increases methylation of CpG sites located at select distances from the dCas9 binding site. Although a shortened linker decreased methylation of other CpGs proximal to the target site, it did not reduce off-target methylation of more distant CpG sites. Instead, targeted mutagenesis of the methyltransferase's DNA binding domain, designed to reduce DNA affinity, significantly and preferentially reduced methylation of such sites.